Chiefs and contestations over power and territory: the case of Njanja of Buhera district, 1950s-2016. - Zhanje, Tavonga (Midlands State University, 2017)
The study looked at chiefs and contestations over power and territory: The case of Njanja people of Buhera District, 1950-2016. The research was motivated by the keenness to find the instability of chieftaincy which was informed by contingent socio-economic and political factors. Contestation over power and territory is the prime problem. This was caused by colonial land policies which started in the 1950s such as the NLHA and the abolition of some chieftaincy that disrupt the customary law of rotational succession system. The study looked at the origins of Njanja tribe, its genealogy and expansion. It also focused on Njanja, chiefly disputes over power and territory. Again, in addition the research looked at the disputes resolution strategies in the Njanja and the effect of contestations over power and territory culturally, economically and politically. The research used various published books such as those written by Weinrich and Holleman. They talked about chiefs in the colonial state and also the book by Jocelyn Alexander which analyses unsettled disputes over land from colonial to post-colonial era in Zimbabwe. These books gave the researcher a clear background of chiefs’ disputes from Rhodesia beyond community development to post-colonial era in Zimbabwe. The dissertation used primary sources such as delineation reports, NADAs from National Archives of Zimbabwe which mapped the history of the Njanja people genealogy and its rotational succession system. Of the major concern, the dissertation used qualitative technique as the methodology of the study.